Age of acquisition affects the retrieval of grammatical category information. Issue 4 (April 2013) - Bai, Lili; Ma, Tengfei; Dunlap, Susan; Chen, Baoguo
This study investigated age of acquisition (AoA) effects on processing grammatical category information of Chinese single-character words. In Experiment 1, nouns and verbs that were acquired at different ages were used as materials in a grammatical category decision task. Results showed that the grammatical category information of earlier acquired nouns and verbs was easier to retrieve. In Experiment 2, AoA and predictability from orthography to grammatical category were manipulated in a grammatical category decision task. Results showed larger AoA effects under lower predictability conditions. In Experiment 3, a semantic category decision task was used with the same materials as those in Experiment 2. Different results were found from Experiment 2, suggesting that the grammatical category decision task is not merely the same as the semantic category decision task, but rather involves additional processing of grammatical category information. Therefore the conclusions of Experiments 1 and 2 were strengthened. In summary, it was found for the first time that AoA affects the retrieval of grammatical category information, thus providing new evidence in support of the arbitrary mapping hypothesis.